Meningkatkan Prestasi Belajar: Pentingnya Self Regulation Learning - Fadli Padila Putra; Riska Rahmawati (CV. Ulil Albab Corp, 2023)
Students who have low self-regulation learning abilities tend to experience difficulties in learning which results in bad attitudes and dependence on others, namely cheating, exams by looking at notes and so on. The purpose of this study is to explain how important self-regulation learning is for students in order to improve student learning achievement. The research method used is library research by making books and scientific journals as a source of data in the process. Self regulation learning is a process in which individuals regulate, supervise, and control their own learning. This involves using cognitive, metacognitive, and behavioral strategies that enable one to become an effective and independent learner. Self regulation learning is a very important ability that must be possessed by every student. When students can organize themselves well in learning, they will avoid problems such as cheating and so on, at the same time it will also affect the increase in student learning achievement.